Classification of costs and methods of their management in the system of strategic control (Economics and region, 2023)
The article discusses the main goals of controlling to improve current processes in the company and achieve strategic goals. It is said that management accounting with its system indicators, reports and cost management is both the information basis and the tools of this process. With the correct organization of management accounting, top management receives all the necessary data to optimize management and improve the production process. However, without proper internal control, it is impossible to manage the economic and production activities of the company. Properly organized management accounting with control functions allows you to avoid many mistakes and financial risks in business. This helps management not only manage the company more effectively, but also develop its future. Strategic management accounting is an accounting and analytical system of information that is important for strategic management decisions of the organization's top management. It is a system for the transformation of data flows and the formation of financial and non-financial indicators that characterize the external and internal conditions of the company's activities, the degree of effectiveness and efficiency of strategy implementation. In today's highly competitive economy, innovations in the strategic management accounting system, including cost optimization models, are increasingly in demand. As a central object of strategic planning, accounting, control and analysis, costs are the most important factor influencing the profitability of the organization, their level and degree of impact management, as well as can be significantly regulated by making strategic decisions. From this point of view, a clear, unambiguous definition of the essence of the category of "expenses" becomes even more relevant. The article also examines the theoretical and methodological aspects of the formation of a management accounting system in the context of a vertically integrated direction of the enterprise's functioning. The relationship between the management accounting system and the process of self-organization is proved, and the significance of the synergistic effect in vertically integrated enterprises for its management is indicated.
Keywords: accounting; strategy; controlling; cost grouping; financial result; evaluation; automation; management accounting; management decision